IMPROVING PERFORMANCE OF SUGARCANE PLANTS IN LESS COMPETITIVE AREAS OF BRAZIL: A STUDY OF THE PERNAMBUCO STATE INDUSTRY (INMR - Innovation & Management Review, 2008)
Brazilian national sugarcane based industry, especially in the Center-South region, is considered the most competitive in the world mainly because of the technological apparatus development and technology diffusion. National sugarcane industry reached the number one world competitive index and efficiency patterns, but the industrial sugarcane cluster located in the Northeast region, did not achieve to follow the other region success in reaching these competitive patterns. Many aspects can explain this gap in competiviness between the two sugarcane production regions. Differences in soil, climatic and topographic conditions are the basic points. In Center-South the harvest is mainly mechanized increasing substantially the production efficiency with great impacts in cost reductions. The substantial difference in cost-efficiency patterns, both in the agricultural and in the industrial systems equilibrium, increases even more the competitiveness gap between these two sugarcane based industrial regions. The main target is to reduce this gap by improving the industrial productivity levels.